Alzheimer’s disease biomarkers in patients with obstructive sleep apnea hypopnea syndrome and effects of surgery: A prospective cohort study - Kong, Weili; Zang, Yi (Frontiers in Aging Neuroscience, 2023)
Background: Obstructive sleep apnea hypopnea syndrome (OSAHS) may cause Alzheimer's disease (AD), 7T-tau, p-tau, Aβ42, and Aβ40 are important elements in the process of AD, and changes in the levels of these biomarkers may affect the cognitive functioning of patients. Our objective was to investigate whether uvulopalatopharyngoplasty could reduce the plasma levels of AD biomarkers in OSAHS patients and the potential correlations of AD biomarkers with cognitive impairment and sleepiness, and explore the independent influencing factors of cognitive function. Methods: AD biomarkers were measured in the plasma of 35 patients with severe OSAHS requiring surgical treatment and 16 healthy controls. The cognitive function and sleepiness of OSAHS patients was also evaluated. The case group was given Uvulopalatopharyngoplasty and followed at the postoperative sixth month, the follow-up cases were 27, and plasma AD biomarker levels, cognitive function, and sleepiness were re-evaluated. The preoperative and postoperative AD biomarker levels OSAHS patients were compared with each other and those of the control group. Spearman correlation analysis and linear regression were used to explore the relationships of AD biomarkers with cognitive impairment and sleepiness. The linear mixed regression analysis was conducted for univariate and multivariable analysis. Results: Significantly higher Aβ40, t-tau, p-tau in plasma were observed preoperatively in OSAHS patients comparing to controls (29.24±32.52 vs. 13.18±10.78, p=0.049; 11.88±7.05 vs. 7.64±4.17, p=0.037; 26.31±14.41 vs. 17.34±9.12, p=0.027). The sixth month of postoperation, the plasma AD biomarkers (Aβ42, Aβ40, t-tau, p-tau) in plasma levels decreased significantly (0.26±0.18 vs. 0.20±0.16, p=0.0001; 33.00±36.00 vs. 23.52±24.46, p=0.0046; 12.02±7.38 vs. 8.88±6.21, p=0.0001; 28.07±15.33 vs. 20.43±10.50, p=0.0001). A comparison of MMSE and ESS scores from before to after surgery revealed obvious differences (26.96±1.72 vs 29.07±1.78, p= 0.0001; 11.33±5.16 vs 5.89 ± 2.83, p=0.0001). Changes in cognitive function and sleepiness scores from before to after Uvulopalatopharyngoplasty were significantly correlated with AD biomarkers. Body mass index and t-tau were potential influencing factors cognitive function. Conclusion: OSAHS can increase plasma AD biomarkers levels. Uvulopalatopharyngoplasty can improve patients' cognition and sleepiness, and the mechanism may be related to changes in plasma AD biomarkers. Overweight and t-tau were identified as independent risk factors for cognitive decline.